2020
DOI: 10.1037/adb0000568
|View full text |Cite
|
Sign up to set email alerts
|

Shared molecular genetic risk of alcohol dependence and posttraumatic stress disorder (PTSD).

Abstract: Alcohol use disorder (AUD) and posttraumatic stress disorder (PTSD) frequently co-occur, highlighting the importance of understanding the etiology of these comorbid conditions. Although AUD and PTSD are moderately heritable with modest overlap in genetic risk as estimated from family studies, there has been a paucity of work using molecular genetic data to estimate shared genetic effects on these conditions. This study used large-scale genomewide molecular data to examine shared genetic risk for AUD, specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
4
28
0
1
Order By: Relevance
“…Consistent with previous work (Sartor et al, 2011;Sheerin et al, 2020), this study found positive genetic correlations between PTSD and AUD-related phenotypes (Max. Alc., AUDIT-P, AUD, AD) among individuals of EA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous work (Sartor et al, 2011;Sheerin et al, 2020), this study found positive genetic correlations between PTSD and AUD-related phenotypes (Max. Alc., AUDIT-P, AUD, AD) among individuals of EA.…”
Section: Discussionsupporting
confidence: 93%
“…However, this effect was driven by women, for whom the genetic correlation was moderate and significant, but not for men (Sheerin et al, 2020). Genetic correlation analyses between PTSD and alcohol consumption were also conducted by our group, finding a non-significant association (rG = -.07; Bountress et al, 2021); another group found near zero genetic correlation between PTSD and the Alcohol Use Disorders Identification Test (AUDIT) consumption score subscale (AUDIT-C) (Mallard et al, 2021).…”
Section: Introductionmentioning
confidence: 49%
“…However, recent large GWAS metanalyses for AC and problematic alcohol use have yielded 99 (Liu et al, 2019) and 29 (Zhou et al, 2020) robustly associated variants, respectively. Few studies to date have examined the genetic correlation between PTSD and AUD using molecular genetic techniques such as linkage disequilibrium score regression (Bulik‐Sullivan et al, 2015), but recent research by our group found a moderate, significant correlation between PTSD and AD (rg = 0.35, Sheerin et al, 2020). To our knowledge, studies have yet to estimate genetic correlations between PTSD and AC.…”
Section: Introductionmentioning
confidence: 93%
“…alcoholism, executive function, post-traumatic stress disorder, trauma (r = .35) and a moderate, but significant correlation between alcohol dependence and PTSD (r = .34) in female participants (Sheerin et al, 2020). Although there are environmental and genetic contributions to both PTSD and alcohol dependence, most studies only examine dichotomous parental alcohol dependence status.…”
Section: Individuals With a Fh Of Alcohol Dependence Have Been Shownmentioning
confidence: 99%
“…Further, Sartor et al showed that PTSD and alcohol dependence had a genetic correlation of 0.54 (Sartor et al., 2011). In addition, a recent study by Sheerin et al on shared molecular genetic basis for alcohol dependence and PTSD showed lower heritability for PTSD and alcohol dependence ( h 2 = 0.18 and 0.09, respectively) and a significant correlation between alcohol dependence and PTSD ( r = .35) and a moderate, but significant correlation between alcohol dependence and PTSD ( r = .34) in female participants (Sheerin et al., 2020). Although there are environmental and genetic contributions to both PTSD and alcohol dependence, most studies only examine dichotomous parental alcohol dependence status.…”
Section: Introductionmentioning
confidence: 97%